Perencanaan Green Manufacturing Pada Usaha Pembuatan Tempe “OJI” di Cimahi Bandung - Winanita, Christiana Maria; Prestianto, Bayu (Universitas Katolik Soegijapranata, Semarang, 2025)
Tempeh Oji is one of the home-based tempeh making businesses that has green manufacturing problems in the form of inadequate waste processing and the owner's lack of knowledge about waste management. Through an assessment of 18 indicators initiated by the OECD (Organization for Economic Co-operation and Development), the aim of this study is to determine the extent of the green ranking and also as a guide for planning the implementation of green manufacturing using government regulations regarding 4R (Recycle, Reduce, Reuse, Recovery) green industry. The approach method used is descriptive qualitative where data is collected using interview, observation and documentation techniques. The results of research conducted on the Tempeh Oji business are that Tempeh Oji has an Advanced in its green rating and meets 14 of the 18 indicators proposed by the OECD. Indicators that are not yet green will later be improved using green manufacturing planning based on Law of the Republic of Indonesia Number 3 of 2014 concerning Industry. The green manufacturing planning carried out at Tempeh Oji applies Recycle, Reduce and Recovery. Tempe Oji is also advised to pay more attention to the cleanliness of its production house and make a simple water filtration to reduce production residue which will later be detrimental to the surrounding community and help Tempe Oji's business to make it easier to process business permits.